Reliability-constrained routing for traffic load balancing in Wireless Sensor Networks - Chughtai, O. (IEEE Computer Society, 2014)
In recent years, a notable progress has been observed in the field of Wireless Sensor Networks (WSNs) due to their enormous number of applications. In this paper, a routing problem has been considered in a static WSN. Traditionally, routing mechanisms are based on a single objective optimisation function, e.g., the cost in terms of distance to find the shortest End-to-End (ETE) path from a source (S) to a destination (D). This behaviour may not be appropriate for long term reliable communication. We have considered a reliability-constrained multi-objective optimisation problem that implicitly captures the traffic load based on the Packet Delivery Ratio (PDR) along with the hop-count. The proposed technique selects an optimum ETE reliable path. The reliability is achieved by selecting the nodes with least congestion along the path from S to D that eventually balance the traffic load in the network. The result shows that the PDR and the hop count have a significant impact to select the best reliable ETE path. Â© 2014 IEEE.